2013
DOI: 10.1177/0268355513481766
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous angioplasty of internal jugular and azygous veins in patients with chronic cerebrospinal venous insufficiency and multiple sclerosis: early and mid-term results

Abstract: Endovascular treatment of the IJV and azygous veins in patients with CCSVI and MS is a safe procedure with no post-procedural complications followed by significant improvement of IJV flow haemodynamic parameters and decrease in the EDSS score. Whether CCSVI percutaneous treatment might affect clinical improvement in patients suffering from MS is yet to be seen after completion of major multicentric clinical trials, still it seems like that this procedure is not negligible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 29 publications
0
12
1
Order By: Relevance
“…CCSVI endovascular treatment is followed by significant improvement of IJV flow hemodynamic parameters and decrease in the EDSS score. 10 In particular CDU showed a significant improvement in cross-sectional area parameters and significant decrease in confluence velocity values associated with a significant decrease in postoperative IJV pressure gradient. 10 However, a post-procedural non-invasive outcome measure to follow-up CCSVI has not been established.…”
Section: Introductionmentioning
confidence: 80%
“…CCSVI endovascular treatment is followed by significant improvement of IJV flow hemodynamic parameters and decrease in the EDSS score. 10 In particular CDU showed a significant improvement in cross-sectional area parameters and significant decrease in confluence velocity values associated with a significant decrease in postoperative IJV pressure gradient. 10 However, a post-procedural non-invasive outcome measure to follow-up CCSVI has not been established.…”
Section: Introductionmentioning
confidence: 80%
“…In recent years percutaneous transluminal angioplasty (PTA) of the internal jugular veins (IJVs) has been used to treat chronic cerebrospinal venous insufficiency (CCSVI), a vascular condition reportedly associated with multiple sclerosis (MS) that is characterized by constricted cerebral venous outflow [ 1 – 5 ]. This has resulted in many thousands of operations being undertaken worldwide, with the PTA procedure that is generally considered to be safe [ 6 8 ]. Despite this, the use of PTA to alleviate CCSVI in MS patients remains controversial [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…1 There is controversy as to the nature of these structural and functional extracranial venous anomalies and whether they even represent pathologic findings, and certainly no agreement exists as to whether there is any etiologic relationship with MS. Several recent prevalence studies that used different imaging techniques have reported large discrepancies in the prevalence of extracranial venous anomalies characterized as CCSVI findings in patients with MS. [2][3][4][5][6][7] Endovascular treatment for these venous anomalies was introduced in an open-label study that included 65 patients with MS with postprocedure follow-up of .18 months. 8 Several subsequent prospective open-label, nonrandomized studies investigated safety and efficacy of venous angioplasty in MS. [9][10][11][12][13][14][15][16][17][18] Findings from some of these studies have generated considerable controversy over potential treatment benefit, which remains unproven, whereas others showed a potential increase in disease activity. 9,10, 19 We investigated safety and efficacy of venous angioplasty in patients with MS exhibiting findings of extracranial venous outflow restrictive anomalies described as hallmarks of CCSVI in the setting of a prospective, double-blind, sham-controlled, randomized pilot trial.…”
mentioning
confidence: 99%
“…24,32,33 Our studies, though suggestive of a venous role in many chronic neurologic diseases including MS, were not quite as strongly supportive as initially reported, 1 nor quite as dismissive as results recently reported. 34 However, given the initial remarkable results, 8,11,12,16,17,35 we attempted to design a study that could address critical aspects of the venous outflow restriction playing a role in MS pathogenesis (CCSVI hypothesis). Therefore, we designed PREMiSe with a double-blinded, sham-controlled design-which was unique for CCSVI interventional studies-knowing that many aspects of this hypothesis remained unsubstantiated but with clearly established biases among physicians and patients.…”
mentioning
confidence: 99%